Connectedness among Northeast Asian Housing Markets and Business Cycles - Hahn Shik Lee; Woo Suk Lee (East Asian Economic Review (EAER), 2020)
This paper investigates the connectedness among housing markets using the methodology developed in Diebold and Yilmaz (2014, 2016). In particular, we examine the international linkages among housing markets in Northeast Asian countries: namely, China, Japan, and Korea. The basic finding is that connectedness measures vary over the business cycle, with a surge during the global financial crisis. However, the international linkages among the three Asian housing markets seem rather weak. By including GDP in the model, we also find that housing market in one country is more affected by its own economic conditions than that of neighboring countries. Given earlier evidence that cross-regional spillover among domestic housing markets is high, this result suggests that housing market connectedness is more of domestic cross-regional phenomena, rather than international ones.
Keywords: C32; E01; R11; 330; Housing Market; Business Cycle; Northeast Asian Region; Connectedness; International Linkage